Insights of curricular supervised intership for geography teacher academic training - Lira Júnior, Fernando César Rocha (Geosaberes; Vol 8 No 14 (2017): Jan - Apr, 2017)
The intership is essential in the formation of any professional, in teacher academic trainig is the moment of contact with the school. This is a reflection on the insights of the Curricular Supervised Intership of  geography teachers academic traning, whereas: laws, conceptions and our experiences around the theme. The general objective is to analyze the contributions of internships. In the specific objectives, intended to identify those laws about the stage; understand the main conceptions of interships along the history of the formation of teachers; reflect on our experiences with the stages, while otherwise commissioning of the course of Geography - UFC. Bibliographical surveys were made about the legislation of the interships, the decade of 40 until 2008. Besides bibliographical searches on the concepts of stage, which have their dichotomy placed before/after the decade of 1990. Were taken in consideration the probationary reports (I, II, III and IV) as a record of our experiences. We conclude that the laws are inadequacies about the activity of intership and need of supervision. Designed as a moment to reflect on teacher praxis, the stage is rich in experiences and reflections on the future teaching profession and the development of technical skills and research.
Keywords: Formação Docente em Geografia; Estágio Supervisionado; Legislação, Concepções e Experiências.